Bixbyite-type Ln2O3 as promoters of metallic Ni for alkaline electrocatalytic hydrogen evolution - Sun, Hongming; Yan, Zhenhua; Tian, Caiying; Li, Cha; Feng, Xin; Huang, Rong; Lan, Yinghui; Chen, Jing; Li, Cheng-Peng; Zhang, Zhihong; Du, Miao (Nature communications, 2022)
The active-site density, intrinsic activity, and durability of Ni-based catalysts are critical to their application in industrial alkaline water electrolysis. This work develops a kind of promoters, the bixbyite-type lanthanide metal sesquioxides (Ln 2 O 3 ), which can be implanted into metallic Ni by selective high-temperature reduction to achieve highly efficient Ni/Ln 2 O 3 hybrid electrocatalysts toward hydrogen evolution reaction. The screened Ni/Yb 2 O 3 catalyst shows the low overpotential (20.0 mV at 10 mA cm −2 ), low Tafel slope (44.6 mV dec −1 ), and excellent long-term durability (360 h at 500 mA cm −2 ), significantly outperforming the metallic Ni and benchmark Pt/C catalysts. The remarkable hydrogen evolution activity and stability of Ni/Yb 2 O 3 are attributed to that the Yb 2 O 3 promoter with high oxophilicity and thermodynamic stability can greatly enlarge the active-site density, reduce the energy barrier of water dissociation, optimize the free energy of hydrogen adsorption, and avoid the oxidation corrosion of Ni. While renewable H 2 evolution will require inexpensive, abundant catalysts, non-noble metals typically show relatively low activities. Here, authors examine lanthanide metal sesquioxide doped metallic Ni and show efficient, stable performances for alkaline H 2 evolution electrocatalysis.